Alectinib in the treatment of ocular metastases of ALK rearranged non small cell lung cancer: Description of 2 case reports - Gozzi, Elisa (Medicine (Baltimore), 2020)
RATIONALE: Choroidal metastasis is a rare metastatic location although the most common intraocular neoplasm. In general, choroidal metastases respond favorably to systemic therapy targeted toward the primary neoplasm. In patients with choroidal metastasis of ALK rearranged non small cell lung cancer (NSCLC), targeted therapy using Alk inhibitors gradually replaced radiotherapy as the best treatment. Alectinib is a second-generation ALK inhibitors. Here we describe 2 clinical cases of patients with choroidal metastasis of ALK rearranged NSCLC who received Alectinib as first-line therapy achieving disease control and quality of life improvement. PATIENTS CONCERNS: In case report 1, 62-year-old man presented with scintillated scotomas at the level of the right eye; in case report 2, 69-year-old man presented with respiratory distress, persistent cough resistant to medical therapy, pain, and blurred vision. DIAGNOSES: In case report 1, fundus and ultrasonographic examination showed circumscribed choroid thickening with dome-like appearance compatible with repetitive lesion. Computed tomographic/y (CT) showed multiple bilateral pulmonary nodular formations and adenocarcinoma of the lung was diagnosed by a transbronchial biopsy. In case report 2, CT showed a primary lesion of 36 × 27 mm in the middle lobe with bilateral lung metastases and lymphadenopathies. Multiple hepatic metastases and minor suspicious bone repetitions. A liver biopsy made a diagnosis of adenocarcinoma compatible with pulmonary primitiveness. An ocular fluoroangiography evidenced a left choroidal metastasis. INTERVENTIONS: Case report 1, 2, medical treatment with Alectinib 1200 mg/day was initiated. OUTCOMES: In case report 1, a few days after beginning the treatment, both systemic symptoms like respiratory distress and low vision were palliated. Reassessment by CT confirmed treatment response. In case report 2, clinically, visus disorders had already improved 2 weeks after beginning treatment. CT showed pulmonary, nodal, and hepatic response. Stability of bone metastases occurred after 2 months. In addition, ocular ultrasonography documented the regression of previously reported lesions confirmed treatment response. LESSONS: Alectinib works very well in intracranial metastases and is assumed to be so on the ocular ones as well, with benefit for the patient in quality of life.